In vitro anticancer efficacy of Calendula Officinalis extract-loaded chitosan nanoparticles against gastric and colon cancer cells - Ozturk, Rabia Yilmaz; Cakir, Rabia (TAYLOR & FRANCIS LTD, 2025)
Objective: This study assessed the anticancer activities of Calendula officinalis-loaded chitosan nanoparticles in gastric and colon cancer cells compared with fibroblast cells and examined the balance between ROS and antioxidants. Methods: Considering this information, we synthesized Calendula officinalis-loaded chitosan nanoparticles (CO-CSNPs) via the ionic gelation method. Their characterizations were carried out with ZetaSizer, UV-Vis, FTIR and SEM devices including size, morphology and surface zeta potential analysis, loading capacity, encapsulation efficiency, in vitro drug release, and chemical interactions. The anticancer activities of CO, CSNPs, and CO-CSNPs were tested against AGS, Caco-2, and normal NIH-3T3 cells using an XTT assay. The anticancer effects were evaluated using DAPI staining, scratch assay, reactive oxygen species (ROS) detection and the CUPRAC method on cellular and non-cellular processes that promote anticancer mechanisms. Results: Results showed that CO and CO-CNPs exhibited anticancer activity against AGS and Caco-2. Further, the formulation of CO with CSNPs enhanced the anticancer activity of CO while having no cytotoxicity on NIH-3T3. DAPI staining, scratch assay, ROS, and CUPRAC method confirmed the anticancer activity of CO and CO-CSNPs, which resulted in a reduction in the number of apoptotic cells, inhibited migration, triggered apoptotic pathway via ROS, and higher antioxidant activity. Conclusions: The results of the study indicate that CO-CSNPs are a promising therapeutic formulation for gastric and colon cancer treatment. We consider that this study will lead to the investigation of molecular mechanisms of CO-CSNPs in cancer treatment and their investigation in clinical studies.
Keywords: Calendula officinalis extract; chitosan; cancer drug carrier; nanoparticle; nanomedicine; Pharmacology & Pharmacy